Low-temperature synthesis of LiMnPO4/RGO cathode material with excellent voltage platform and cycle performance. (20th January 2017) - Fu, Xiaoning; Chang, Kun; Li, Bao; Tang, Hongwei; Shangguan, Enbo; Chang, Zhaorong
Graphical abstract: The cocoon-like C-LiMnPO4/G nanocomposites have a higher discharge specific capacity, high voltage platform and high rate cycle performance. Highlights: Cocoon-like LiMP/RGO were directly synthesized via a one-step liquid-phase at low temperature. The content of GO has a great influence to the particle size and the morphology of LMP/RGO. The proposed C-LMP/G has excellent voltage platform and high rate cycle performance. Abstract: Pure and well-crystallized LiMnPO4 /reduced graphene oxide (RGO) nanopowders are synthesized by adding a small amount glucose and graphene oxide simultaneously in dimethyl sulfoxide (DMSO)/H2 O, under constant atmospheric pressure and at low-temperature (108 °C). The scanning electron microscopy (SEM) and transmission electron microscopy (TEM) images show that the addition of different amounts of graphene oxide can significantly affect the particle size and morphology of LiMnPO4 /RGO composites. With small amounts of graphene oxide (1 and 3 wt.%), the small LiMnPO4 particles are wrapped in RGO, in a cocoon-like structure. This special morphology can be maintained after a rapid carbon coating treatment at high temperature. Electrochemical studies show that these cocoon-like C-LiMnPO4/G nanocomposites not only have a higher discharge specific capacity, but also show improved high voltage platform and high rate cycle performance. When the added graphene oxide is 3%, the specific capacity of C-LiMnPO4 /G nanocomposite is 160.8 mAh g −1 at 0.05 C, the discharge capacity in the area of more than 4.0 V is up to 115 mAh g −1, accounting for 70% of the total discharge capacity. The proposed C-LiMnPO4 /G nanocomposites also exhibit an outstanding high rate capability, where the discharge specific capacity at 1C can reach to 99.6 mAh g −1 and after 1000 cycles at 5 C, it still has 83% of capacity retention.